Real-time velocity measurement to linear motion of a rigid object with monocular image sequence analyses - Filitto, Danilo (2016)
This paper presents a methodology and all procedures used to validate it, which were executed in a physics laboratory under controlled and known conditions. The validation was based on the analyses of registered data in an image sequence and the measurements acquired by high precision sensors. This methodology intended to measure the velocity of a rigid object in linear motion with the use of an image sequence acquired by commercial digital video camera. The proposed methodology does not need a stereo pair of images to calculate the object position in the 3D space: it needs only images sequence acquired for one, only one, angle view (monocular vision). To do so, these objects need to be detected while in movement, which is conducted by the application of a segmentation technique based on the temporal average values of each pixel registered in N consecutive image frames. After detecting and framing these objects, specific points belonging to the object (pixels), on the plane image (2D coordinates or space image), are automatically chosen, which are then transformed into corresponding points in the space object (3D coordinates) by the application of collinearity equations or rational functions (proposed in this work). After obtaining the coordinates of these points in the space object that are registered in the sequence of images, the distance, in meters, covered by the object in a particular time interval may be measured and, consequently, its velocity can be calculated. The system is low cost, use only a computer (architecture Intel I3), and a webcam used to acquire the images (640 × 480, 30 fps). The complexity of the algorithm is linear, fact that allows the system to operate in real time. The results of the analyses are discussed and the advantages and disadvantages of the method are presented.